Fault Detection for Discrete-Time Nonlinear Impulsive Switched Systems. (2nd August 2015) - Su, Qingyu; Jia, Xiaolong; Song, Zhengfan
Abstract : This paper investigates the fault detection problem for discrete-time nonlinear impulsive switched systems. Attention is focused on designing the fault detection filters to guarantee the robust performance and the detection performance. Based on these performances, sufficient conditions for the existence of filters are given in the framework of linear matrix inequality; furthermore, the filter gains are characterized by a convex optimization problem. The presented technique is validated by an example. Simulation results indicate that the proposed method can effectively detect the faults.